Mucinase-engineered cell membrane nanovesicles degrade the glycocalyx shield to potentiate antitumor immunity - Xiaorui Geng; Silan Liu; Yuanwei Pan; Yun Ge; Lang Rao (Proceedings of the National Academy of Sciences, 2026)
The tumor glycocalyx forms a protective shield that masks checkpoint proteins and compromises the efficacy of immunotherapies. While the bacterial protease StcE can degrade this barrier by cleaving O-glycosylated mucin domains, its therapeutic potential is hindered by off-target toxicity and high immunogenicity. To overcome these limitations, we developed a biomimetic platform of cell membrane fusion nanovesicles (FNVs) that codisplay StcE and CD47 nanobodies (nCD47) for spatially controlled glycocalyx degradation and enhanced checkpoint blockade. Using the SpyTag/SpyCatcher system, we generated StcE-displaying NVs, which were then fused with nCD47-displaying NVs. The resulting StcE-nCD47-FNVs retained potent mucin-hydrolyzing activity and exhibited well-defined physicochemical properties. By removing the mucin barrier, StcE-nCD47-FNVs significantly enhanced nCD47 binding to CD47 on tumor cells, thereby potentiating antitumor immune responses. More importantly, benefiting from prolonged circulation of FNVs and tumor targeting of nCD47, the StcE-nCD47-FNV platform demonstrated superior tumor accumulation and biosafety compared to free StcE. In murine models of colorectal and breast cancer, StcE-nCD47-FNVs significantly suppressed tumor growth and metastasis by remodeling the tumor microenvironment, as evidenced by increased M1 macrophage polarization and CD8 + T cell infiltration. By integrating glycocalyx engineering with vesicle nanotechnology, StcE-nCD47-FNVs offer a safe, robust, and versatile strategy to breach the tumor glycocalyx for next-generation cancer immunotherapy.